The role of a multidisciplinary team meeting in an antiretroviral treatment programme - C van deventer; M Radebe (AOSIS, 2009)
Abstract Introduction The multidisciplinary team at the wellness clinic, Potchefstroom hospital has been having regular meetings since the clinic was accredited as a treatment site for HAART. The meetings have concentrated on patients who have experienced problems on treatment. The aim was to understand and overcome barriers to adherence and any other patient related issues at the clinic. Method. Minutes of 2006 were audited in order to acquire an understanding of the difficulties faced by patients and to investigate outcomes of corrective interventions. Results 17% of the files could not be traced in order to obtain more information. 36% of patients had stabilized with improved or undetectable viral loads. Alcohol and work related matters played an important role in poor adherence. There were however many other factors identified